A Simulation to Improve Understanding and Communication of Ethical Dilemmas That Surround Brain Death - Nicholas Ludka; Ngan Nguyen; Daniel Menkes; Abram Brummett (Association of American Medical Colleges, 2024)
Introduction Providers across multiple specialties may be called upon to perform brain death assessments at hospitals that lack specialty neurology or critical care services. To address this need, we developed a brain death curriculum involving simulation and group discussion to prepare medical trainees for brain death testing and communication with surrogate decision-makers. Methods A 1-hour session was delivered to trainees rotating through the intensive care unit at William Beaumont University Hospital. One trainee per session participated in a simulation involving a brain-dead patient (SimMan 3G Mannequin) and spouse (confederate) while the remainder of the cohort observed from a separate room. The trainee briefed the spouse about the brain death examination, performed the examination, and communicated their findings. Afterward, the cohort discussed the history, law, and common ethical and communication issues that surround brain death. Results A total of 35 trainees participated from August 2022 to March 2023. After the session, trainees were more comfortable performing brain death testing (p < .001), responding to ethical issues (p < .001), and communicating with families (p < .001). However, the session did not change their frustration with family members who have a circulatory (p = .72) or high brain (p = .52) view of death. Discussion The simulation had a positive impact on medical trainees' ability to perform brain death testing and their comfort level in discussing complex ethical issues that surround brain death. Our results support continued simulation training for medical trainees to better prepare them for clinical practice.